2021
DOI: 10.1002/ccd.29887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on in‐hospital mortality and 90‐day readmissions in patients undergoing transcatheter edge‐to‐edge mitral valve repair: Analysis from the National Readmission Database

Abstract: Background: Patients undergoing transcatheter edge-to-edge mitral valve repair (TEER) carry a high risk of rehospitalization due to disease, procedure, patient, hospital, and system related factors.Aims: We aimed to explore the impact of gender on in-hospital mortality and 90-day readmissions in patients undergoing TEER.Methods: We utilized the National Readmission Database from 2012 to 2018 to identify individuals who underwent TEER for mitral regurgitation. Gender-based differences in in-hospital mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In contrast, in another study that evaluated sex differences in post-TEER readmissions, 90-day readmissions were significantly higher in women compared to men (30.2% vs. 25.4%, p < 0.001). 12 This observation was supported by Goel et al, 32 who found an association between female sex and higher readmission rates following both surgical mitral valve repair and replacement. Potential explanations for higher readmissions in females following TEER and mitral valve surgery include: (a) women tend to be frailer and older at the time of TEER compared to men; 33 (b) women tend to have more comorbidities with delayed referral for intervention; 34 (c) women tend to have less improvement in New York Heart Association (NYHA) functional status and more frequent residual ≥grade III MR at follow-up compared to men; 33 (d) women have a higher rate of concomitant tricuspid valve disease leading to residual tricuspid regurgitation after mitral TEER and worse clinical outcomes; 35 (e) anatomical abnormalities including bileaflet mitral prolapse are reported more often in women; 36 (f) the degree of calcification in mitral stenosis are noted to be higher in women.…”
Section: All-cause 90-day Readmissionmentioning
confidence: 72%
See 4 more Smart Citations
“…In contrast, in another study that evaluated sex differences in post-TEER readmissions, 90-day readmissions were significantly higher in women compared to men (30.2% vs. 25.4%, p < 0.001). 12 This observation was supported by Goel et al, 32 who found an association between female sex and higher readmission rates following both surgical mitral valve repair and replacement. Potential explanations for higher readmissions in females following TEER and mitral valve surgery include: (a) women tend to be frailer and older at the time of TEER compared to men; 33 (b) women tend to have more comorbidities with delayed referral for intervention; 34 (c) women tend to have less improvement in New York Heart Association (NYHA) functional status and more frequent residual ≥grade III MR at follow-up compared to men; 33 (d) women have a higher rate of concomitant tricuspid valve disease leading to residual tricuspid regurgitation after mitral TEER and worse clinical outcomes; 35 (e) anatomical abnormalities including bileaflet mitral prolapse are reported more often in women; 36 (f) the degree of calcification in mitral stenosis are noted to be higher in women.…”
Section: All-cause 90-day Readmissionmentioning
confidence: 72%
“…Congruently, in a study that evaluated sex differences following TEER, in-hospital mortality rates were identical in males and females (2.1% vs. 2.1%; p = 0.908). 12 However, in a previous study that evaluated sex differences in TAVR outcomes, women had higher in-hospital mortality compared to men (2.7% vs. 2.3%; p = 0.002). 11 The higher rate of in-hospital mortality in women following TAVR was attributed to several factors: (a) women had higher Society of Thoracic Surgery Predicted Risk of Mortality (STS-PROM) scores; (b) higher rates of vascular and bleeding complications in women compared to men; (c) greater use of non-femoral access due to inadequate femoral vessel caliber in women compared to men, which has been shown in numerous studies to have worse outcomes compared to femoral access; 25 (d) higher rates of conversion from TAVR to open surgery in women for complications such as annular rupture.…”
Section: In-hospital Mortalitymentioning
confidence: 88%
See 3 more Smart Citations